Materials science, testing and informatics VII : selected, peer reviewed papers from the 9th Hungarian Conference on Materials Science October 13-15, 2013, Balatonkenese, Hungary - Berecz, T. (Materials science forum, 2015)
Collection of selected, peer reviewed papers from the 9 th Hungarian Conference on Materials Science, October 13-15, 2013, Balatonkenese, Hungary. The 75 papers are grouped as follows: Session I. - Materials and Technologies; Session II. - Materials Testing; Session III. - Modelling.